Sistem Informasi Akuntansi Kas Kecil Menggunakan Metode Dana Berubah - Fidya Arie Pratama; Nining Rahaningsih; Lili Purani; Nurhadiansyah (Politeknik Negeri Cilacap, 2019)
Based on the results of observations made, it was found that the lack of research locations have not been able to produce financial statements presentation about petty cash expenses accurately, quickly, and accurately. That is because there is no accounting information system that covers the process of receiving and disbursing petty cash. At present in the presentation of petty cash financial statements still use Microsoft Office Excel where the summing errors can occur due to accidental deletion of the formula, resulting in the addition of errors that are more difficult for beginners to learn. The change fund system method is a system in which the amount of the petty cash fund changes according to the expenditure and receipt or addition of petty cash. In designing this information system using methods with the stages of Requirements analysis, Data modeling, Normalization. This study also uses the PHP (Hypertext Preprocessor) programming language, XAMPP, my sql, sublime text 3, Microsoft Office Vision and data obtained from the results of data collection at the research location. This petty cash accounting information system is made so that the process of presenting financial statements about petty cash expenditures that are urgently needed by the company can be done easily, quickly, accurately, effectively, and efficiently in order to avoid waste and fraud. This accounting information system is designed to manage expenses and receipts or additions to petty cash that are sufficient to monitor and control petty cash expenditures.